Pengaruh Komitmen Organisasional Dan Budaya Organisasi Terhadap Organizational Citizenship Behaviour - Yunita - Christy; Sinta - Setiana; Puput - Cintia (Universitas Kristen Maranatha, 2018)
The key to success in a change is my source of human being as an initiator and agent of continuous change, the formation of a process and culture that together enhance the ability of organizational change.Organizational Citizenship Behavior (OCB) is able to increase the effectiveness and success of the organization in the long term. OCB is a positive behavior of people in the organization, which is expressed in the form ofwillingness to be conscious and voluntary to work beyond the tasks that should be. In the world of work, a person's commitment to an organization or company is often an important issue. The commitment of all individuals in the organization or often referred to as organizational commitment can provide more value to the company in achieving its goals. Organizational effectiveness can also be enhanced by creating a culture that will lead to the achievement of organizational goals (Ismail, 2008). The population in this study is a Private Bank in Bandung. The sample in this study are employees who work in private banks. The statistical method used in this study is multiple regression.Research results show that organizational commitment influences organizational citizenship behavior, organizational culture influences organizational citizenship behavior and organizational commitment and organizational culture influence organizational citizenship behaviour.Â Keywords: Organizational Commitment, Organizational Culture, Organizational Citizenship Behaviour